-81dB PSRR regulated cascode fully MOS bandgap reference for power management in RF energy harvesting systems - M. K.Zulkalnain; N. A.Kamsani; R. M.Sidek; F. Z.Rokhani; S. J.Hashim; M. N.Hamidon (Institute of Advanced Engineering and Science, 2019)
In the midst of technological advance where everything is connected via the internet, IoT is emerging as a potential solution to everything, ranging from health wearables to smart city. An RFEH power management system has promising benefits that could further improve the powering of IoT devices as it has potential for clean energy as well as other advantages which consists of a rectifier, bandgap reference and LDO as the main core. However, the main challenge is supplying clean and low noise power to sensitive circuits such as low power sensors, VCOs and PLLs. A high PSRR bandgap reference that rejects noise at the power supply is needed so that the circuitry powered by RFEH systems would be able to function properly. This paper presents a bandgap with MOS PTAT and CTAT extraction achieving a PSRR of -81dB at a Vref of 0.415V was designed on 130nm CMOS technology targeting IoT RFEH devices that operate at sub-threshold and near-threshold region that exhibits improvement over the base design.